Cultural Sentinels: Ọkọnkọ Society's Watchdog Role in Conflict Resolution and Cultural Preservation in Umuahia Community - Aniga, Ugo (Journal of Contemporary Rituals and Traditions, 2024)
Purpose of the Study: This study investigates the diverse roles of the Ọkọnkọ Society in Umuahia, Nigeria, particularly its use of Igbo language and cultural practices in conflict resolution and cultural preservation, challenging the conventional view of the society as merely a secret male cult. Methodology: The study employs qualitative, ethnographic methodologies including in-depth interviews, FGDs, and non-participant observations in Umuahia, supplemented by scholarly literature, with analysis grounded in hermeneutics, semiotics, and conflict management theories to emphasize the role of language and culture in the Ọkọnkọ Society's practices. Main Findings: The research uncovers the crucial role of the Ọkọnkọ Society in Umuahia as a guardian of peace and cultural sentinel. Key findings include the society's use of Igbo proverbs and semiotics (e.g., ọmụ palm frond, uhie drum) in conflict mediation, and the societal respect and trust they command. The society's conflict resolution role extends beyond mere mediation, effectively acting as an appellate court within the community, especially in land disputes. The study also highlights society's role in preserving and enforcing cultural norms and practices. Applications of this Study: This research has practical implications for understanding indigenous conflict resolution mechanisms in African communities. It offers insights for policymakers and social workers in designing culturally sensitive conflict management strategies. Additionally, it contributes to preserving the cultural heritage of the Igbo people by documenting traditional practices and societal structures. Novelty/Originality of this Study: This study is original in its comprehensive examination of the Ọkọnkọ Society, linking Igbo language and culture with conflict management practices. It fills a significant gap in academic research by shedding light on the societal and cultural dynamics within the Umuahia community, thus providing a deeper understanding of the intricate relationship between language, culture, and social governance in an African context.